Evaluation of difficult airway in paediatric population ranging from 5-12 years age group - S. Sumer, Sushmita; C. Cham, Soma; M. Raipure, Amrusha; Dhumane, P.G. (International Journal of Medical Research and Review, 2019)
Background: The aim of this study is to predict difficult airway on the basis of various airway assessment parameter in the paediatric population between 5-12 years age group. To assess the value of modified Mallampati test (MMT), upper-lip-bite test (ULBT), thyromental distance (TMD), ratio of height to thyromental distance (RHTMD) from which Cormack Lehane grade was derived to predict difficult airway i.e. difficult intubation in paediatric patients ranging from 5-12 years age. Material and Methods: 100 ASA grade I & II paediatric patients of either sex between the age group of 5-12 years posted for elective surgery under general anaesthesia requiring endotracheal intubation were included in the study. Modified Mallampati test, upper lip bite test, thyromental distance and ratio of height to thyromental distance of the patients were measured and recorded. All the distances were measured with the help of a flexible measuring tape so as to measure the distances accurately. Results: Modified Mallampati test has the highest sensitivity (75%) and specificity (92.05%) among all the other screening tests. It also has high positive predictive value (56.25%), negative predictive value (96.43%) and diagnostic accuracy (90%). Upper Lip Bite test has high specificity (79.55%) and negative predictive value (93.33%) with high diagnostic accuracy (77%). It has a sensitivity of 58.33% which is similar to the sensitivity of thyromental distance and ratio of height to thyromental distance. Thyromental distance has high specificity (65.90%) with high negative predictive value (92.06%). Conclusion: Modified Mallampati test is a useful bedside screening test for predicting difficult intubation in patients between 5-12 years age group. The Upper Lip bite test and thyromental distance has high specificity with high negative predictive value and diagnostic accuracy. The ratio of height to thyromental distance is least useful predictor of airway assessment.